Elements of cultural scripts of trauma sequelae among trauma victims in East Africa - Mutuyimana, Celestin; Maercker, Andreas (Frontiers in Psychology, 2023)
Post-traumatic experiences are usually hurtful for trauma survivors. However, their diagnostic and appropriate interventions usually fall into the Western categorization of mental disorders and do not necessarily fit all contexts and cultures. This may result in inadequate care of post-traumatic consequences and low utilization of mental health services. This study incorporated the voice of trauma survivors and experts in the domain in East Africa to provide subjective perceptions and interpretation of post-traumatic experiences in their context, referred to as cultural scripts of trauma elements. Further emphasis was given to the relationship between these elements and cultural value orientations. The results revealed different elements that indicate the specific and culture-based experience of trauma survivors in this sample and the cultural values that are related to post-traumatic experiences. The study expands the literature on traumatic stress and creates an avenue to facilitate the diagnosis and treatment of the long-term effects of trauma with culturally adapted interventions. It opens the way for following studies aiming to develop cultural script instruments and explore the temporal relationships between cultural script elements in different cultures.